Observed climate change hotspots. Issue 9 (12th May 2015) - Turco, M.; Palazzi, E.; von Hardenberg, J.; Provenzale, A.
Abstract We quantify climate change hotspots from observations, taking into account the differences in precipitation and temperature statistics (mean, variability, and extremes) between 1981–2010 and 1951–1980. Areas in the Amazon, the Sahel, tropical West Africa, Indonesia, and central eastern Asia emerge as primary observed hotspots. The main contributing factors are the global increase in mean temperatures, the intensification of extreme hot‐season occurrence in low‐latitude regions and the decrease of precipitation over central Africa. Temperature and precipitation variability have been substantially stable over the past decades, with only a few areas showing significant changes against the background climate variability. The regions identified from the observations are remarkably similar to those defined from projections of global climate models under a "business‐as‐usual" scenario, indicating that climate change hotspots are robust and persistent over time. These results provide a useful background to develop global policy decisions on adaptation and mitigation priorities over near‐time horizons.